The Influence of Using Pinterest Application Media in Learning News Text Writing Skills - Dermawanto Gultom; Harlen Simanjuntak; Vina Merina Br Sianipar (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Pinterest is a free photo and video sharing application where inspiration grows and creativity thrives. This application offers a visually rich and idea-oriented experience to its users. Its focus is on discovery, creativity, and organization, making it an attractive learning medium. This study aims to describe: 1) the results of the pre-test of news text writing skills; 2) the results of the post-test of news text writing skills in learning using the Pinterest application media. This study uses a descriptive quantitative method with a quasi-experimental type through a one group pretest-posttest design in the 2025/2026 academic year at SMA Swasta Hosana, Medan. The population of this study was all students of grade XI.A of SMA Swasta Hosana, Medan who took the pre-test, learning news text writing skills using the Pinterest application media, and took the post-test of news text writing skills, totaling 31 students. The sample was determined at 31 students based on a statistical formula. The research instruments were news text writing tests and lesson plans as well as Pinterest application media. Quantitative data were analyzed using parametric inferential statistics, namely one-sample t-test for the first and second objectives and paired sample t-test for the third objective because the requirements of normality and homogeneity were met. The results of the study showed: 1) the mean pre-test of the ability to write news texts of class XI.A students of SMA Swasta Hosana, Medan was 16.84 or 52.63 percent (categorized as low); 2) the mean post-test of the ability to write news texts of class XI.A students of SMA Swasta Hosana, Medan was 26.00 or 81.25 (categorized as high); 3) the Pinterest application media was proven to be effective in learning the ability to write news texts. The t-value of the paired sample test was -19.363 with a sig. 0.00 <0.05 so that Ho was rejected.